Pengaruh Pemberian Streptozotocin Dosis Tunggal terhadap Kadar Glukosa Tikus Wistar (Rattus norvegicus) - Nihayah Enis Munjiati (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Diabetes Mellitus (DM) is a disease caused by metabolic disorders in the pancreas, which is characterized by an increased glucose levels or hyperglycemia due to decreased insulin levels from the pancreas. In animal research, DM is often caused by administration of diabetogenic agents. Streptozotocin works by forming free radicals that can damage the pancreatic beta cells; therefore, insulin production can be disrupted. This study aims to determine the glucose level on Wistar Rats (Rattus norvegicus) before and after a single dose streptozotocin-induced. This study was conducted experimentally with a posttest-interpretation design with a control group design. The result demonstrated that the average blood glucose level before the induction of streptozotocin was 92,63 (SD 10,487) mg/dL, after being induced by streptozotocin was 235,56 (SD 164,929) mg/dL with a difference of 142,938 (SD 160,543) mg/dL. In this study, it can be concluded that the induction of a single dose of streptozotocin has an effect on increasing blood glucose levels on Wistar Rats (Rattus norvegicus).